2015
DOI: 10.1103/physrevc.92.014612
|View full text |Cite
|
Sign up to set email alerts
|

Isobaric yield ratio difference between the140AMeVNi58+Be

Abstract: Background: The isobaric yield ratio difference (IBD) method is found to be sensitive to the density difference of neutron-rich nucleus induced reaction around the Fermi energy.Purpose: An investigation is performed to study the IBD results in the transport model. Methods:The antisymmetric molecular dynamics (AMD) model plus the sequential decay model GEMINI are adopted to simulate the 140A MeV 58,64 Ni + 9 Be reactions. A relative small coalescence radius Rc = 2.5 fm is used for the phase space at t = 500 fm/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…( 2) has been used to determine T [34,35]. In the IBD analysis, ∆µ/T from the small A fragment changes very little [45,[47][48][49][50][52][53][54], which means that ∆µ/T can be canceled out in the difference between the IYRs in Eqs. ( 2) and ( 3).…”
Section: Isobaric Ratio Difference Thermometermentioning
confidence: 99%
See 2 more Smart Citations
“…( 2) has been used to determine T [34,35]. In the IBD analysis, ∆µ/T from the small A fragment changes very little [45,[47][48][49][50][52][53][54], which means that ∆µ/T can be canceled out in the difference between the IYRs in Eqs. ( 2) and ( 3).…”
Section: Isobaric Ratio Difference Thermometermentioning
confidence: 99%
“…In the isoscaling or the IBD methods, the fragments in the two reactions are assumed to have the same temperature, which can make it possible to cancel out the free energy of the fragments [47,49,53] (in the recent Shannon information uncertainty method, this is not required [54]). Since T IB is obtained from fragments, it is interesting to check whether T IB is the same in the dif- ferent reactions.…”
Section: A ∆B and ∆Lnr Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using different approximations of free energy for fragment, equation (2) has been used to determine T from IMFs [42,43]. It has been shown that in the IBD analysis m D T determined by the small-A fragment changes very little [33][34][35][36][37][38][39]50], indicating that m D T can be canceled out in the difference between the IYRs in equations (2) and (3). Defining the difference between IYRs in equations ( 2) and (3), one has,…”
Section: Methodsmentioning
confidence: 99%
“…Besides, the temperature is difficult to be separated from the probes to investigate the nuclear matters in HICs. For example, in the isoscaling method [26][27][28][29], the isobaric-yield-ratio (IYR) methods [21,[29][30][31][32] and the isobaric-yield-ratio-difference (IBD) method [33][34][35][36][37][38][39][40][41], the ratios of chemical potential to temperature entirely are taken as probes.…”
Section: Introductionmentioning
confidence: 99%